2014
DOI: 10.1136/injuryprev-2013-040999
|View full text |Cite
|
Sign up to set email alerts
|

The association of graduated driver licensing with miles driven and fatal crash rates per miles driven among adolescents

Abstract: Background Graduated driver licensing (GDL) laws are associated with reduced crash rates per person-year among adolescents. It is unknown whether adolescents crash less per miles driven or drive less under GDL policies. Methods We used data from the US National Household Travel Survey and Fatality Analysis Reporting System for 1995–1996, 2001–2002, and 2008–2009. We compared adolescents subject to GDL laws with those not, by estimating adjusted incidence rate ratios for being a driver in a crash with a death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Previous studies have also suggested heterogeneity between adolescents aged 16 and 17 years. 17,38 Adult supervision or restrictions on night driving and number of underage passengers, all of which should be most common among adolescents aged 16 years, but as adolescents become older and these restrictions are removed, the influence of GDL on 17-year-olds could be less. In addition, graduation from GDL is possible at age 17 years in most states, particularly if the adolescent takes a driver education course.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also suggested heterogeneity between adolescents aged 16 and 17 years. 17,38 Adult supervision or restrictions on night driving and number of underage passengers, all of which should be most common among adolescents aged 16 years, but as adolescents become older and these restrictions are removed, the influence of GDL on 17-year-olds could be less. In addition, graduation from GDL is possible at age 17 years in most states, particularly if the adolescent takes a driver education course.…”
Section: Discussionmentioning
confidence: 99%
“…Seatbelt laws with primary enforcement for front seat passengers were binary coded as present/absent. Graduated drivers licensing (GDL), which places additional restrictions on young or inexperienced drivers, can modify youths’ driving behaviors [45]. GDL laws were binary coded by state-quarter-year as present/absent.…”
Section: Methodsmentioning
confidence: 99%
“…From 2001–2002 to 2008–2009, the average number of annual trips and kilometers for drivers/passengers decreased for all three age groups (16, 17, 20–24). This might be linked with the economic recession and high unemployment during 2008–2009 [ 28 ]. By including persons aged 20–24 years in our model, and adjusting for temporal changes in crash rates over time among those covered and not covered by a GDL law in each teenage age group, we sought to control for non-GDL factors that influence travel over time [ 13 , 21 , 22 , 28 ].…”
Section: Discussionmentioning
confidence: 99%